2008
DOI: 10.1016/j.ejphar.2008.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Ketanserin, a 5-HT2 receptor antagonist, decreases nicotine self-administration in rats

Abstract: Nicotine intake constitutes a principal mechanism for tobacco addiction. In addition to primary effects on nicotinic acetylcholine receptors, nicotine has cascading effects, which may underlie its neurobehavioral actions. Nicotine induces serotonin (5-HT) release, which has not classically been thought to be involved in tobacco addiction. However, addiction can be characterized more as a disorder of compulsion than a disorder of enjoyment. 5-HT mechanisms play key roles in compulsive disorders. Nicotine-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 34 publications
4
37
1
Order By: Relevance
“…Serotonergic systems are quite complex with a wide variety of receptor subtypes. We have found that ketanserin, a 5-HT 2A and 5-HT 2C antagonist, significantly reduces nicotine self-administration in rats (Levin et al, 2008). The relative involvement of serotonin 5-HT 2A and 5-HT 2C receptors is not clear from this study, but it is known that 5-HT 2C receptors located in the ventral tegmental area provide inhibitory influence over dopaminergic projections that are important for drug reinforcement (Bubar and Cunningham, 2007).…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Serotonergic systems are quite complex with a wide variety of receptor subtypes. We have found that ketanserin, a 5-HT 2A and 5-HT 2C antagonist, significantly reduces nicotine self-administration in rats (Levin et al, 2008). The relative involvement of serotonin 5-HT 2A and 5-HT 2C receptors is not clear from this study, but it is known that 5-HT 2C receptors located in the ventral tegmental area provide inhibitory influence over dopaminergic projections that are important for drug reinforcement (Bubar and Cunningham, 2007).…”
Section: Introductionmentioning
confidence: 62%
“…We previously showed in rats that ketanserin, a 5-HT 2A and 5-HT 2C antagonist, significantly reduces nicotine self-administration (Levin et al, 2008). The differential role of 5-HT 2A versus 5-HT 2C receptors was not clear from that study.…”
Section: Discussionmentioning
confidence: 84%
“…Indeed local infusion of M100907 to the VTA blocked amphetamine-and cocaine-induced locomotion [ 47 , 106 ]. Consistently, it has recently been shown that vulnerability of adult male rats to hyperactivity, induced by cocaine, is enhanced following virally mediated overexpression of 5-HT 2A receptors in the VTA [ 108 ]. Due to this evidence, and the relationship between the VTA and reinforcing effects of nicotine, it may be expected that 5-HT 2A receptor antagonists would modify some of the behavioural effects observed following the administration of nicotine.…”
Section: -Ht 2a Receptorsmentioning
confidence: 75%
“…This comparison of drug effects on IV nicotine self-administration with the operant lever pressing and licking was conducted to help determine which neural systems are more or less involved in the consummatory aspects of nicotine self-administration. In recent studies with the operant lever press method, we have found that the serotonin 5HT 2A and C antagonist ketanserin (Levin et al, 2008) and the histamine H 1 antagonist pyrilamine (Levin et al, 2011c) were effective in reducing nicotine self-administration. We studied these antagonists of 5HT 2A and C and H 1 receptors because these receptor subtypes are two of the more prominent actions of the antipsychotic drug clozapine, which has been found to reduce smoking significantly in people with schizophrenia (McEvoy et al, 1995, McEvoy et al, 1999).…”
Section: Introductionmentioning
confidence: 99%